Protective RNA nanovaccines against Mycobacterium avium subspecies hominissuis - Touray, Bubacarr J.B.; Hanafy, Mostafa; Phanse, Yashdeep; Hildebrand, Rachel; Talaat, Adel M. (Frontiers in Immunology, 2023)
Induction of effective immune response is critical for the success of mRNA-based therapeutics. Here, we developed a nanoadjuvant system compromised of Quil-A and DOTAP (dioleoyl 3 trimethylammonium propane), hence named QTAP, for the efficient delivery of mRNA vaccines constructs into cells. Electron microscopy indicated that complexation of mRNA with QTAP forms nanoparticles with average size of 75 nm and have 90% encapsulation efficiency. Incorporation of pseudouridine modified mRNA resulted in higher transfection efficiency and protein translation with low cytotoxicity than unmodified mRNA. When QTAP-mRNA or QTAP alone transfected macrophages, pro-inflammatory pathways (e.g., NLRP3, NF-kb, and MyD88) were upregulated, an indication of macrophage activation. In C57Bl/6 mice, QTAP nanovaccines encoding Ag85B and Hsp70 transcripts (QTAP-85B+H70) were able to elicit robust IgG antibody and IFN- ɣ, TNF-α, IL-2, and IL-17 cytokines responses. Following aerosol challenge with a clinical isolate of M. avium ss. hominissuis (M.ah), significant reduction of mycobacterial counts was observed in lungs and spleens of only immunized animals at both 4- and 8-weeks post challenge. As expected, reduced levels of M. ah were associated with diminished histological lesions and robust cell-mediated immunity. Interestingly, polyfunctional T-cells expressing IFN- ɣ, IL-2, and TNF- α were detected at 8 but not 4 weeks post challenge. Overall, our analysis indicated that QTAP is a highly efficient transfection agent and could improve the immunogenicity of mRNA vaccines against pulmonary M. ah, an infection of a significant public health importance, especially to the elderly and to those who are immune compromised.